Decoding the specific minty-like aroma of ‘Rucheng baimaocha’ (camellia pubescens) black tea - Jian Ouyang; Ronggang Jiang; Huimin An; Xingchang Ou; Jing Wang; He Xie; Wenjie Fu; Jing Zhang; Hongyu Chen; Qi Liu; Juan Li; Haitao Wen; et al. (Food Chemistry: X)
Rucheng Baimaocha (Camellia pubescens) black tea (RCBT) exhibits floral and sweet attributes with a unique minty-like aroma, distinguishing it from traditional and other innovative black teas. However, its key odorants remain unknown. In this study, gas chromatography-olfactometry (GC-O) combined with aroma extraction dilution analysis detected 26 aroma-active compounds (ACCs), of which 20 ACCs were quantified as odorants of RCBT infusion. In addition, aroma recombination models well simulated the overall aroma characteristics of RCBT infusion, which proved the accuracy of identification and quantification. Omission experiments showed that 12 key odorants played crucial roles in aroma formation of RCBT. Among these, four odorants (methyl salicylate, (E, Z)-2,6-nonadienal, methyl geranate, and (E)-2-nonenal), were of great importances for unique minty-like aroma, with significantly higher concentrations compared to other black tea varieties. This study offered a foundational theoretical framework for the processing and quality control of RCBT.